SAT0303 Effect of Hmg-Coa Reductase Inhibitor Drugs (Statins) on Systemic Lupus Erythematosus Disease Activity: A Systematic Review and Meta-Analysis. (15th July 2016) - Garcia, G.M.; Urbano, A.; Salido, E.
Abstract : Background: Statins have a known effect in reducing the morbidity and mortality due to atherosclerosis. Recently, statins have been proposed to have anti-inflammatory and immunomodulatory effects. In in-vitro studies these drugs inhibit inflammatory cells like monocytes, macrophages, and lymphocytes, decrease the expression of major histocompatibility complex (MHC) and decrease adhesion molecules and inflammatory cytokines such as IL6 and IL10, that are also implicated in SLE pathogenesis. In terms of immunomodulary effects, animal studies demonstrated that statins exacerbate or trigger cellular apoptosis and induce a shift in the Th1/Th2 balance leading to B-cell reactivity and production of pathogenic autoantibodies. Also it has been found that Treg cells can be unstable in the periphery and may promote autoimmunity. These may promote preexisting autoimmune conditions to progress toward clinical disease, such as SLE. Statins have not been widely studied in SLE. The existing studies mostly have primary endpoints on the evaluation of atherosclerosis, and in terms of disease activity, these studies showed contradicting results. Thus, we sought to determine the effect of statins on the disease activity of SLE based on the best available evidence. Methods: To identify relevant publications on statins and SLE disease activity, a systematic literature search of PubMed, Scopus, and Cochrane databases was done with no date and language restrictions. Included studies were on adult SLE patients. Only randomized controlled trials that used statins as intervention and reported SLE disease activity as an outcome measure were included. Two reviewers did quality appraisal, risk bias assessment, and data extraction. Results: Three studies have met the eligibility criteria and were included in this review. Quantitative synthesis was then done. The pooled analysis of these studies suggests that statins have no significant effect on disease activity on random effects model with an overall effect of 0.13 (P=0.90, 95% CI -1.65, 1.88). Conclusions: Statins neither increased nor decreased SLE disease activity; therefore possibly it can be safely given to SLE patients without the risk of triggering or exacerbating a flare. Disclosure of Interest: None declared